Three Ecological Models to Evaluate the Effectiveness of Trichoderma spp. for Suppressing Aflatoxigenic Aspergillus flavus and Aspergillus parasiticus - Nataliia Voloshchuk; Zilfa Irakoze; Seogchan Kang; Joshua J. Kellogg; Josephine Wee (Toxins, 2024)
Chemical pesticides help reduce crop loss during production and storage. However, the carbon footprints and ecological costs associated with this strategy are unsustainable. Here, we used three in vitro models to characterize how different Trichoderma species interact with two aflatoxin producers, Aspergillus flavus and Aspergillus parasiticus, to help develop a climate-resilient biological control strategy against aflatoxigenic Aspergillus species. The growth rate of Trichoderma species is a critical factor in suppressing aflatoxigenic strains via physical interactions. The dual plate assay suggests that Trichoderma mainly suppresses A. flavus via antibiosis, whereas the suppression of A. parasiticus occurs through mycoparasitism. Volatile organic compounds (VOCs) produced by Trichoderma inhibited the growth of A. parasiticus (34.6 ± 3.3%) and A. flavus (20.9 ± 1.6%). The VOCs released by T. asperellum BTU and T. harzianum OSK-34 were most effective in suppressing A. flavus growth. Metabolites secreted by T. asperellum OSK-38, T. asperellum BTU, T. virens OSK-13, and T. virens OSK-36 reduced the growth of both aflatoxigenic species. Overall, T. asperellum BTU was the most effective at suppressing the growth and aflatoxin B1 production of both species across all models. This work will guide efforts to screen for effective biological control agents to mitigate aflatoxin accumulation.